Students' Mathematical Argumentation with the Visualizer Cognitive Style in Proving the Congruence of Triangles - Indahwati, Rohmah; Basri, Hasan (JagoMIPA: Jurnal Pendidikan Matematika dan IPA, 2024)
The use of axiomatic deductiveism, perception problems, mathematical visual representations and how students convey arguments as a bridge in proving geometric problems are obstacles that are often faced by students. This research aims to describe how prospective mathematics teacher students who have a visualiser cognitive style convey their mathematical arguments in explaining proofs related to triangle congruence. The subjects of this research were selected from students who have a visualizer cognitive style who had previously been given a cognitive style questionnaire. The research subjects consisted of 3 subjects, each with high (S1), medium (S2) and low (S3) mathematics abilities. Data were analyzed using Toulmin argumentation components. The research results show that S1 provides proof based on correct claims, providing fairly complete data both from the question statement and additional data resulting from the subject's reasoning which is used to decide on the claim. The subject uses several warrants and is supported by logical backing to connect the data with the claim. For S2 and S3 to provide final answers or false claims, they have incomplete data as a basis for deciding claims because the subject is mistaken in representing the image and is deep in mathematical literacy related to errors in describing the visualization in the image.